Peningkatan Ketahanan Keluarga Dalam Menghadapi Pandemi Covid-19 Melalui Vaksin dan Pembuatan Ramuan Herbal Peningkat Sistem Imun - Asih Triastuti; Riyanto; Yon Haryanto; Arde Toga Nugraha (Universitas Mataram, 2022)
Since it was declared a pandemic by the World Health Organization, Covid-19 has significantly altered the behavior and way of life of the global community, as well as the majority of the Indonesian people. This has ramifications for the resilience of families. A strong family resilience will benefit the family's ability to deal with the various impacts and changes caused by the pandemic and post-pandemic problems. According to various reports, community empowerment is critical to the pandemic's success. Communities with a strong health culture, educational and social foundation will be successful in responding to, analyzing, and resolving pandemics (and other health/social problems that may arise) using quantifiable strategies that can actively support the government policies. The purpose of this activity is to foster a society with physically and mentally healthy, educated, and has a healthy culture. The Pucung-Umbulsari village is located 24 kilometers from the campus of the Univesitas Islam Indonesia, is a partner in this service. Promotional activities for the covid-19 vaccine and the workshop of herbals to boost the immune system are carried out based on the results of the initial need assessment conducted by the proposer and community officials (heads of RT and RW). The activities are part of the community recovery process, which includes addressing issues that arose during the pandemic and preparing people to adapt to new normal. While maintaining health protocols, health promotion activities and training are conducted. The social impact of this community service activity are an increase in public awareness of the COVID-19 vaccine in preventing the spread of the disease and the high participation and initiative of the society to produce herbals.